Rethinking Automatist Interdisciplinarity: The Relationship between Dance and Music in the Early Choreographic Works of Jeanne Renaud and Françoise Sullivan, 1948-1950 - Lindgren, Allana (Circuit, 2011)
This article considers the role of music within the context of the Montréal automatists by addressing the choreographic works created by Jeanne Renaud and Françoise Sullivan during the late 1940s and early 1950s. In so doing, it becomes clear that the dance activities of these two choreographers often paralleled contemporaneous experiments in music. Renaud and Sullivan’s collaborations with Pierre Mercure were particularly successful and ultimately demonstrate that music was a significant part of the Automatists’ history, even though Mercure was not a signatory to the Automatist manifesto, Refus Global.